Literature Review: The Potencial Effect of Dandang Gendis Leave (Clinacanthus nutans Lindau) - Kusumaningtyas Siwi Artini; Weri Veranita; Tatiana Siska Wardani (Proceeding of International Conference on Science, Health, And Technology, 2021)
Indonesian are used to use herb to medicate a disease. One of the medicinal plants used is Clinacnathus nutans (Burm.f.) Lindau. Clinacnathus nutans Lindau is a traditional plant, commonly known as dandang gendhis (Java – Indonesia), ki tajam (Sunda – Indonesia), belalai gajah (Malaysia), Sabah Snake Grass (Singapore), and phaya yo (Thailand). It belonging to the Acanthaceae family. This study aimed to find out the the effect of giving the extract of Clinacnathus nutans Lindau to subject. This research method was using literature review. The information about Clinacanthus nutans Lindau collected from an online database such as Pub Med, Scient direct and Google Scholar. The number of chemical compound were identified from leaves. It contain of alkaloid, flavonoid, polifenol, saponin and tanin Some of the potential effect shown such as antihypoglycemic, antioxidant and anticancer, and analgetic. In this study,we can conclude that in the future Clinacnathus nutans Lindau is valuable to use as herbal medicine with more investigation.